Aspirations and compromises: Changes in homestead space relations of the extreme poor after Disaster - Rahman, Tahmina (© 2011 PLOS Currents, 2016)
This article was published in PLoS Currents [© 2011 PLOS Currents] and the definite version is available at : https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3205995/